Design of Photographic Lens for a Nanosatellite Used in Commercial Remote Monitoring of the Earth - Krzysztof HOLAK; Hubert ADAMCZYK; Daria KAWKA; Piotr PARUCH (Communications of International Proceedings, 2025)
The growing use of nanosatellite platforms for Earth observation missions requires optical systems that combine compactness, low mass, and high imaging performance under extreme environmental conditions. Existing research has primarily focused on satellite integration and sensor electronics, leaving a gap in detailed methodologies for the design and qualification of nanosatellite photographic lenses. This study addresses this gap by presenting the complete optical and mechanical development process of a catadioptric lens intended for nanosatellite-based remote sensing. The optical design was modeled using Code V software to determine key parameters, including focal length, f-number, and diffraction-limited resolution. A laboratory prototype was fabricated and subjected to a comprehensive series of qualification tests, including modulation transfer function (MTF) analysis with Imatest Master, high-temperature exposure, ultra-high vacuum evaluation, and vibration endurance testing. The system was then integrated with the Światowid nanosatellite and deployed into orbit via the Cygnus NG-11 mission for in-space validation. Both laboratory and orbital results confirmed that the optical assembly maintained focus stability, mechanical integrity, and imaging resolution within design limits. The prototype achieved an MTF50 of approximately 860 LW/PH, consistent with simulation predictions. The findings demonstrate that lightweight catadioptric lenses can provide thermally stable, high-resolution imaging suitable for nanosatellite Earth observation missions, establishing a verified methodology for future optical payload development.
Keywords: Nanosatellite optics; optical systems design; remote sensing technology